A corpus-based analysis of two crucial steps in Business Management research articles: The creation of a research space and the statement of limitations - Mur-Dueñas, Pilar (Nordic Journal of English Studies, 2012)
English has been established as the Language for Research Publication Purposes in many disciplinary fields. Many scholars worldwide, therefore, face linguistic and rhetorical difficulties when writing their academic texts for publication in an L2. This paper focuses on a quantitative and qualitative analysis of two key steps of the research article: the creation of a gap in the Introduction and the statement of limitations in the Discussion. A corpus of 24 research articles in the field of Business Management are analysed in terms of the frequency of use, length and type of metadiscoursal language most commonly used in the phrasing of these two key moments of this academic genre in which authors clearly need to “market” their research. The results may be useful for designing materials and offering informed guidance to (novice) non-native writers when drafting their RAs in English in this discipline.